2021
DOI: 10.3390/toxins13090665
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbents Reduce Aflatoxin M1 Residue in Milk of Healthy Dairy Cow Exposed to Moderate Level Aflatoxin B1 in Diet and Its Exposure Risk for Humans

Abstract: This study investigated the effect of moderate risk level (8 µg/kg) AFB1 in diet supplemented with or without adsorbents on lactation performance, serum parameters, milk AFM1 content of healthy lactating cows and the AFM1 residue exposure risk in different human age groups. Forty late healthy lactating Holstein cows (270 ± 22 d in milk; daily milk yield 21 ± 3.1 kg/d) were randomly assigned to four treatments: control diet without AFB1 and adsorbents (CON), CON with 8 μg/kg AFB1 (dry matter basis, AF), AF + 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, Queiroz et al (2012) and Intanoo et al (2020) reported that when cows exposed to naturally contaminated diets contained 22.28 µg/kg of AFB1 resulted in a significant drop in both protein concentration and fat yield of milk. Furthermore, Cha et al (2021) illustrated that there were no significant differences in milk components (milk fat, protein, lactose, and SCC) of the dairy cows fed with the moderate risk level of (8 g/kg of diet dry matter) AFB1with or without adsorbents. Moreover, Xiong et al (2015) and Gonçalves et al (2017) proclaimed that multiple factors worked behind the aflatoxin M1 excretion amount into raw milk like; AFB1 cow's dietary levels, stage of lactation, milk yield, mammary gland condition, and individual receptivity.…”
Section: Discussionmentioning
confidence: 96%
“…However, Queiroz et al (2012) and Intanoo et al (2020) reported that when cows exposed to naturally contaminated diets contained 22.28 µg/kg of AFB1 resulted in a significant drop in both protein concentration and fat yield of milk. Furthermore, Cha et al (2021) illustrated that there were no significant differences in milk components (milk fat, protein, lactose, and SCC) of the dairy cows fed with the moderate risk level of (8 g/kg of diet dry matter) AFB1with or without adsorbents. Moreover, Xiong et al (2015) and Gonçalves et al (2017) proclaimed that multiple factors worked behind the aflatoxin M1 excretion amount into raw milk like; AFB1 cow's dietary levels, stage of lactation, milk yield, mammary gland condition, and individual receptivity.…”
Section: Discussionmentioning
confidence: 96%
“…Experience from the carry-over studies [ 1 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] shows that aflatoxin consumed with contaminated feed appears relatively quickly (within a few hours after consumption) in milk as AFM1, reaches its maximum within a few days, and its level quickly falls when the source of contamination is eliminated from feed.…”
Section: Aflatoxin In the Cow’s Bodymentioning
confidence: 99%
“…It is reported that clay products have not consistently prevented decreases in milk yield caused by AFB1 ingestion, and yeast fermentation products have been reported to have potential to improve animal performance parameters [ 42 ]. More recent studies have focused on the combined application of clays and yeast [ 17 , 24 , 42 , 44 , 45 , 46 , 67 ] or the use of natural compounds, particularly phytogenic compounds, such as curcumin and curcuminoids from turmeric powder [ 68 ]. A short summary of the reviewed studies is provided in Appendix A .…”
Section: Main Factors Influencing Aflatoxin Carry-overmentioning
confidence: 99%
See 2 more Smart Citations